Solving nonlinear master equation describing quantum damping by virtue of the entangled state representation - 范洪义 任刚 胡利云 姜年权 (Chinese physics B, 2010)
This paper solves the newly constructed nonlinear master equation dρ/dt = κ[2f （N） aρ （1/f （N - 1））a^＋ -a^＋aρ- ρa^＋a], where f（N） is an operator-valued function of N = a^＋a, for describing amplitude damping channel, and derives the infinite operator sum representation of quasi-Kraus operators for the density operator. It also shows that in this nonlinear process the initial pure number state density operator will evolve into the binomial field （a mixed state） when f （N） = 1√N ＋ 1.